The Effect of Using Catalyst in Transesterification Reaction on the Biofuels Quality from Sardine Flour Oil Waste - Sahubawa, Latif; Ningtyas, Diah Probo (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2011)
Process of the transesterification reaction of sardine flour oil waste with NaOH as base catalyst in producing biofuels was conducted. The research purpose has studied the influence of NaOH concentration in transesterification process and examinate its effect on the quality of biofuels production, conversion, and physic quality. The variables that analysed was the effect of NaOH concentration as catalyst (0.5%, 1.0%, 1.5%, and 2.0% from amount of oil and methanol) in the transesterification reaction step. The result showed that the increasing NaOH concentration (0.5% until 1.5%), enhanced the biofuel conversion (%). The highest conversion of biofuels was achieved by using 1.50% NaOH (w/w) with 45.34% biofuels conversion. The major component in the biofuels was methyl palmitate (20.31%). ASTM analysis data also supported that the biofuel product was in agreement with automotive diesel fuel specification. Keywords: catalyst, transesterification, biofuels, quality, wastes